2007
DOI: 10.3758/bf03194076
|View full text |Cite
|
Sign up to set email alerts
|

Visual layout modulates Fitts’s law: The importance of first and last positions

Abstract: When a target in the last position of a structured visual array is aimed for, movement times (MTs) are shorter than predicted by Fitts's law (Adam, Mol, Pratt, & Fischer, 2006). That study, however, confounded relative target position with absolute target location. To determine whether target position does, indeed, produce changes in the speed-accuracy trade-off function, the present experiment manipulated relative target position (e.g., first or last) independently of absolute target location (e.g., nearest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
33
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 26 publications
(21 reference statements)
6
33
1
Order By: Relevance
“…According to the criterion developed by Gan and Hoffmann (1988), all movements should have required visual control. Pratt et al (2007) obtained the results shown in Fig. 2.…”
Section: Introductionsupporting
confidence: 48%
See 4 more Smart Citations
“…According to the criterion developed by Gan and Hoffmann (1988), all movements should have required visual control. Pratt et al (2007) obtained the results shown in Fig. 2.…”
Section: Introductionsupporting
confidence: 48%
“…The present case of the Pratt et al (2007) data is different for the first and last targets, since there was no constraining target on one side of these targets. In the Pratt et al study, the distance between adjacent targets (17 -11.2 = 5.8 mm) was smaller than any reasonable finger width (see below for finger width discussion).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations